Decreased lipases and fatty acid and glycerol transporter could explain reduced fat in diabetic morbidly obese. (6th August 2014) - Ferrer, Roser; Pardina, Eva; Rossell, Joana; Baena‐Fustegueras, Juan Antonio; Lecube, Albert; Balibrea, José María; Caubet, Enric; González, Oscar; Vilallonga, Ramón; Fort, Jose Manuel; Peinado‐Onsurbe, Julia
<x xml:space="preserve">Abstract</x> Objective The possible differences were investigated in 32 morbidly obese patients depending on whether they were "healthy" or had dyslipidemia and/or type 2 diabetes. Methods Lipid metabolism and insulin resistance were analyzed in subcutaneous (SAT) and visceral adipose tissue (VAT) before and during 6 and 12 months after Roux‐en‐Y gastric bypass. Results Significant differences have been found in lipoprotein lipase (LPL) and hormone‐sensitive lipase (HSL) activities in SAT from the different obese group versus normal weight (control) but not between them. The reduced lipase activities in VAT were 43 and 19% smaller (22 and 4% smaller, respectively, vs. control) than the "healthy" obese group for LPL and HSL, respectively, and were accompanied with a reduced expression of these lipases, as well as decreased expression of FAT/CD36, FABP4, and AQ7 in that tissue. In addition, the expression of the other genes measured showed a downregulation not only versus the "healthy" obese but also versus the normal weight group. Conclusions Being obese is not "healthy, " but it is even less so if morbidly obese patients with diabetes and dyslipidemia were considered. The reduced fat accumulation in these patients may be attributed to the decrease of the expression and activity of the lipases of their adipose tissue.